Transparansi Organisasi Perangkat Daerah dalam Penyelenggaraan Pelayanan Publik Pada Era Otonomi Daerah - Windari Irom Putri, Fatimah Malahayati (Universitas Airlangga, 2021)
Abstract The importance of transparency in local government is a concern in this study, especially the close relationship between local government and citizens. This study aims to determine the transparency of regional apparatus organizations in the implementation of public services in the era of regional autonomy with a case study at the Surabaya City Trade Office. This study uses a descriptive qualitative approach. The research locus at the Surabaya City Trade Office. The steps of collecting research data are through observation, in-depth interviews and literature study. Stages of checking the validity of the data using data triangulation. Analysis of research data using qualitative analysis of the interactive model. The conclusion of the research on the transparency of the Surabaya City Trade Office in the process of providing business license services is not yet fully open; related to the ease of regulations and service procedures not yet fully understood by the public in the process of applying for a business license; On the aspect of ease of obtaining information regarding various aspects of public service delivery, there are still people who have difficulty.AbstrakPentingnya transparansi dalam pemerintah lokal menjadi perhatian dalam penelitian ini, terutama hubungan erat antara pemerintah daerah dan warga. Studi ini bertujuan mengetahui transparansi organisasi perangkat daerah dalam penyelenggaraan pelayanan publik pada era otonomi daerah dengan studi kasus pada Dinas Perdagangan Kota Surabaya. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Lokus penelitian di Dinas Perdagangan Kota Surabaya. Langkah pengumpulan data penelitian melalui observasi, wawancara mendalam dan studi pustaka. Tahapan pemeriksaan keabsahan data menggunakaan triangulasi data. Analisis data penelitian menggunakan analisis kualitatif model interatif. Kesimpulan penelitian transparansi Dinas Perdagangan Kota Surabaya pada proses penyelenggaraan pelayanan izin usaha belum sepenuhnya terbuka; terkait kemudahan peraturan dan prosedur pelayanan belum sepenuhnya dipahami oleh masyarakat pada proses mengajukan surat izin usaha; pada aspek kemudahan untuk memperoleh informasi mengenai berbagai aspek penyelenggaraan pelayanan publik masih ada masyarakat yang kesulitan.